Answer:
<h2>-63</h2>
Step-by-step explanation:
<h3>= > x + 38 = - 25 </h3><h3>= > x = - 25 - 38 </h3><h3>= > x = - 63...ans</h3>
<h2>HOPE IT HELPS YOU!!!! </h2>
Step-by-step explanation:
multiplying expressions.
remember every term of one expression has to be multiplied with every term of the other expression, and the results are added up (while considering their individual signs, of course).
1.
(-3×3 + 2x - 4)(3x - 2)
(-9 + 2x - 4)(3x - 2)
(-13 + 2x)(3x - 2) = -13×3x + -13×-2 + 2x×3x + 2x×-2 =
= -39x + 26 + 6x² - 4x = 6x² - 43x + 26
2.
let's do the other multiplication and compare the result with the result of 1 :
(-13 + 2x)(2x - 3) = -13×2x + -13×-3 + 2x×2x + 2x×-3 =
= -26x + 39 + 4x² - 6x = 4x² - 32x + 39
no, this product is not the same as in 1.
There you go. I assumed you know how to derrivate!
Answer: 18°
Step-by-step explanation:
Complementary angles are any two angles whose sum is 90 degrees. Hence, if angles x and y are complimentary, we can say
x + y = 90°
Therefore, the complimentary angle of 72° is obtained by subtracting 72° from 90°
i.e 90° - 72° = 18°
Thus, the complimentary angle of 72° is 18°
Answer:
X-intercepts are also called zeros, roots, solutions, or solution sets.